The efficacy of fluoropyrimidine-based adjuvant chemotherapy on biliary tract cancer after R0 resection. Issue 1 (December 2017) - Kim, Young; Jeong, Chi-Young; Song, Haa-Na; Kim, Tae; Kim, Hong; Lee, Young-Joon; Hong, Soon
Abstract Background The optimal treatment strategy for biliary tract cancer (BTC) after curative-intent resection remains controversial. The purpose of this study was to evaluate the efficacy of fluoropyrimidine-based adjuvant chemotherapy for BTC patients undergoing microscopically margin-negative (R0) resection. Methods We retrospectively analyzed the clinical data of BTC patients who underwent curative-intent R0 resection. Patients were eligible if they received either fluoropyrimidine-based adjuvant chemotherapy or observation after R0 resection. Results A total of 153 patients were included. In the entire patient cohort, no significant differences were observed in 5-year overall survival (OS) rates (48.4% vs. 39.6%, P = 0.439) or 3-year recurrence-free survival (RFS) rates (49.1% vs. 39.5%, P = 0.299) between patients who received fluoropyrimidine-based adjuvant chemotherapy or observation. However, for patients with stages II and III BTC, chemotherapy significantly improved 5-year OS rate (52.4% vs. 35.6%, P = 0.002) and 3-year RFS rate (55.5% vs. 39.1%, P = 0.021) compared with observation. Conclusion Fluoropyrimidine-based adjuvant chemotherapy may prolong the survival of patients with stages II and III BTC after R0 resection.